Vaccine potential of HLA‐A2 epitopes from Leishmania Cysteine Protease Type III (CPC). (28th July 2017) - Dikhit, M. R.; Amit, A.; Singh, A. K.; Kumar, A.; Mansuri, R.; Sinha, S.; Topno, R. K.; Mishra, R.; Das, V. N. R.; Pandey, K.; Sahoo, G. C.; Ali, V.; et al.
Summary: Although the precise host‐defence mechanisms are not completely understood, T‐cell‐mediated immune responses are believed to play a pivotal role in controlling parasite infection. In this study, the potential HLA*A2 restricted peptides were predicted and the ability of peptides to bind HLA‐A*02 was confirmed by a MHC stabilization assay. Two of the peptides tested stabilized HLA‐A*02: (a) LLATTVSGL (P1) and (b) LMTNGPLEV (P3). The potential of the peptides to generate protective immune response was evaluated in patients with treated visceral leishmaniasis as well as in healthy control subjects. Our data suggest that CD8 + T‐cell proliferation against the selected peptide was significantly higher compared to unstimulated culture conditions. The stimulation of peripheral blood mononuclear cells with epitopes individually or as a cocktail upregulated IFN‐γ production, which indicates its pivotal role in protective immune response. The IFN‐γ production was mainly in a CD8 + T‐cells‐dependent manner, which suggested that these epitopes had an immunoprophylactic potential in a MHC class I‐dependent manner. Moreover, no role of the CD3 + T cell was observed in the IL‐10 production against the selected peptides, and no role was found in disease pathogenesis. Further studies on the role of these synthetic peptides may contribute significantly to developing a polytope vaccine idea towards leishmaniasis.